2009
DOI: 10.1007/s10669-009-9233-5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic levels of heavy metals in canned sardines consumed in Nigeria

Abstract: Samples of some popular brands of canned sardines in soybean oil in the Nigerian market were analyzed for levels of cadmium, lead, iron, cobalt, nickel, manganese, chromium, copper and zinc after wet digestion with acids by graphite furnace atomic absorption spectrophotometry. The mean concentrations for the metals in the different brands were as follows: cadmium 0.11-0.26 lg/g, iron 8.04-48.18 lg/g, cobalt 0.01-7.23 lg/g, nickel 0.04-3.26 lg/g, manganese 0.64-1.37 lg/g, chromium 0.01-0.10 lg/g, copper 0.10 lg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 13 publications
2
16
5
Order By: Relevance
“…Children, as well as adults, who lose the ability to remove excess Mn from their bodies, develop nervous system problems. According to the ATSDR, there is no information on the carcinogenicity of this element (Hussein, & Khaled, 2014), and also 0.64 µg/g w.wt to 1.71 µg/g w.wt for canned sardines consumed in Nigeria (Iwegbue et al, 2009). A comparison of our findings with other studies is shown in Table 3.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Children, as well as adults, who lose the ability to remove excess Mn from their bodies, develop nervous system problems. According to the ATSDR, there is no information on the carcinogenicity of this element (Hussein, & Khaled, 2014), and also 0.64 µg/g w.wt to 1.71 µg/g w.wt for canned sardines consumed in Nigeria (Iwegbue et al, 2009). A comparison of our findings with other studies is shown in Table 3.…”
Section: Discussionmentioning
confidence: 47%
“…The results of the present study showed that the highest mean concentration of Fe with an average of 77.53 µg/g wet weight was found in Kawakawa samples. Iron concentration in the literature was reported between 8.04 µg/g w.wt to 48.18 µg/g w.wt for canned sardines consumed in Nigeria (Iwegbue, Nwajei, Arimoro & Eguavoen, 2009). Table 3 shows a comparison of Fe concentration in the canned fish from Iran with some other regions reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The digestion process was carried out by a procedure previously described by Iwegbue et al (2009) with slight modification. Five gram of the homogenized sample was weighed into a 50 mL beaker, and then 20 mL of 65% HNO 3 , 4 mL of 62% HClO 4 and 4 mL of 36% HCl were added into the sample and heated to 120 C for 2 h. The digest was cooled to room temperature, filtered through Whatman No.…”
Section: Sample Preparationmentioning
confidence: 99%
“…[31] The detrimental effects of these metals to human development, growth, and overall health have been well-established. [11,19,[32][33][34] Indeed, sea turtle tissues with heavy metal concentrations at levels toxic to humans have been reported; [13,35,36] including two studies where the eggs of leatherbacks from Western Costa Rica [37] and Loggerheads from Florida, USA [38] contained sufficiently high concentrations of Cd and Hg, respectively, to surpass the provisional tolerable weekly intake of each metal. [39,40] However, there is significant variation in bioaccumulation on metals in marine turtles among species, [41][42][43][44][45][46][47][48][49][50][51] and among locations, even at a small geographical scales.…”
Section: Introductionmentioning
confidence: 99%